2007
DOI: 10.1093/glycob/cwm117
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Profiles of the Prostate Specific Antigen in Free and Complexed Forms from the Prostate Cancer Patient Serum and in Seminal Plasma: a Glycopeptide Approach

Abstract: The oligosaccharide structures of prostate specific antigen (PSA) are expected to be useful in discriminating prostate cancer from benign conditions both accompanied by increased serum PSA levels. A large proportion of PSA forms a covalent complex with a glycoprotein, alpha(1)-antichymotrypsin, in human blood. In the present study, the glycan profiles of free and complexed forms of PSA from cancer patient serum and of seminal plasma PSA were compared by analyzing the glycopeptides obtained by lysylendopeptidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 24 publications
8
79
0
Order By: Relevance
“…In the same study, we observed a different proportion of alpha 2-3 linked sialic acid in the PSA present in patients, which was decreased in relation to that from healthy seminal plasma (15 vs. 25%) (Tabares et al, 2006). However, our present results are more consistent with the observations made by other authors (Ohyama et al, 2004;Tajiri et al, 2008).…”
Section: N-glycosylation Of Psa 2-de Subforms In Prostate Cancer: Chasupporting
confidence: 92%
See 2 more Smart Citations
“…In the same study, we observed a different proportion of alpha 2-3 linked sialic acid in the PSA present in patients, which was decreased in relation to that from healthy seminal plasma (15 vs. 25%) (Tabares et al, 2006). However, our present results are more consistent with the observations made by other authors (Ohyama et al, 2004;Tajiri et al, 2008).…”
Section: N-glycosylation Of Psa 2-de Subforms In Prostate Cancer: Chasupporting
confidence: 92%
“…The low amount of PSA in sera is, however, the limiting step to fully characterize the glycan structures of PSA. So far, few groups have reported the detailed glycan structures of serum PSA from PCa patients (Tabares et al, 2006;Tajiri et al, 2008). Taking into account that the PSA 2-DE subforms (F1-F5) show different proportions between BPH and PCa sera (Sarrats et al, 2010), in this work we have characterized by N-glycan sequencing these 2-DE spots of PSA samples from PCa patients' sera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their profiles did not necessarily show particular similarity to the one reported recently for serum PSA derived from prostate cancer (PC) patients, except for ␣2-3 Sia increment. It should be mentioned, however, that serum PSA level is abnormally high (Ͼ10 g/ml serum) in these patients (35). From a clinical viewpoint, it is important to differentiate PSA glycoforms of malignant prostate cancer from benign prostate hyperplasia.…”
Section: Fabrication Of Antibody-overlay Lectinmentioning
confidence: 98%
“…Seemingly, differences exist in fucosylation and sialylation of KLK3 from prostate cancer patients, although they do not appear to be sufficient for reliable prognosis of the disease (Tabares et al, 2006(Tabares et al, , 2007. Nevertheless, these differences have the potential to discriminate between benign and malignant prostate disease, e.g., by monitoring the complex of KLK3 with anti-chymotrypsin, by using fucosylation analysis, mass spectrometry or lectin microarrays and immunosorbent assays (Tajiri et al, 2008;Dwek et al, 2010;Sarrats et al, 2010;Yan Li et al, 2011).…”
Section: The Prostatic Klks 2 Andmentioning
confidence: 99%